2004
DOI: 10.1105/tpc.019042
|View full text |Cite
|
Sign up to set email alerts
|

Interchromatid and Interhomolog Recombination in Arabidopsis thaliana

Abstract: Intermolecular recombination events were monitored in Arabidopsis thaliana lines using specially designed recombination traps consisting of tandem disrupted b-glucuronidase or luciferase reporter genes in direct repeat orientation. Recombination frequencies (RFs) varied between the different lines, indicating possible position effects influencing intermolecular recombination processes. The RFs between sister chromatids and between homologous chromosomes were measured in plants either hemizygous or homozygous f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(122 citation statements)
references
References 38 publications
2
120
0
Order By: Relevance
“…The ku70 (Riha et al , 2002), wee1 (De Schutter et al , 2007), and rad51 (Li et al , 2004) mutants were described previously. The reporter line uidA/IC9C was used as described in Molinier et al (2004) and the pCDKB1;1:GUS line as in Boudolf et al (2004). The mutant CDKA;1 T14D;Y15E is published in Dissmeyer et al (2009), the cdkb1;1 cdkb1;2 double mutant in Nowack et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…The ku70 (Riha et al , 2002), wee1 (De Schutter et al , 2007), and rad51 (Li et al , 2004) mutants were described previously. The reporter line uidA/IC9C was used as described in Molinier et al (2004) and the pCDKB1;1:GUS line as in Boudolf et al (2004). The mutant CDKA;1 T14D;Y15E is published in Dissmeyer et al (2009), the cdkb1;1 cdkb1;2 double mutant in Nowack et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…However, the detection service provider for that study analysis confirmed that they had tested for PCR inhibitors through inhibition tests and did not find any such molecules (Schoel & Fagan, 2009). In addition, recombination in homozygous or hemizygous (at least two times less) transgenic plants can occur (Molinier, Ries, Bonhoeffer, & Hohna, 2004). Therefore, some events can take place in the target DNA sequences that might avoid or make difficult primer annealing.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to homologous recombination between single-copy sequences, unequal interhomolog and interchromatid recombination between duplicated sequences ( Figure 2) has been observed in yeast (JACKSON and FINK 1981;JACKSON and FINK 1985;KLEIN 1984;KLEIN and PETES 1981;MOTOVALI-BASHI et al 2004;SZOSTAK and Wu 1980;THOMPSON and STAHL 1999), tobacco (TOVAR and LICHTENSTEIN 1992) and Arabidopsis (ASSAAD and SIGNER 1992;JELESKO et al 1999;MOLINIER et al 2004;OPPERMAN et al 2004). Also similar to equal recombination, unequal interchromatid recombination predominated during mitosis in a study conducted in yeast (JACKSON and FINK 1981), whereas unequal interhomolog recombination was preferred in meiosis (JACKSON and FINK 1985).…”
Section: Meiotic Recombination Among Tandemly Arrayed Duplicate Genesmentioning
confidence: 99%
“…Even so, the findings that 1) rates of unequal recombination at Al-b were higher in the presence of a homolog than in its absence (i.e., hemizygotes) and 2) recombinants isolated from marked hétérozygotes most often showed an exchange of flanking phenotypic markers (LAUGHNAN 1949;LAUGHNAN 1952), were interpreted to suggest that the homolog is the preferred recombination template (LAUGHNAN 1952). More recently, molecular characterizations in plants have documented both meiotic interhomolog (ASSAAD and SIGNER 1992;MOLINIER et al 2004;TOVAR and LICHTENSTEIN 1992) and interchromatid (ASSAAD and SIGNER 1992;JELESKO et al 1999;MOLINIER et al 2004;TOVAR and LICHTENSTEIN 1992) unequal recombination events. Meiotic unequal recombination events isolated from synthetic direct repeats in Arabidopsis (MOLINIER et al 2004) and synthetic inverted repeats in tobacco (TOVAR and LICHTENSTEIN 1992) were conducted using both homozygotes (in which recombination can occur either between homo logs or sister chromatids) and hemizygotes (in which recombination can occur only between sister chromatids).…”
Section: Region-specific Trans-acting Modifiers Have Been Characterizmentioning
confidence: 99%
See 1 more Smart Citation